Groundwater potential zones mapping of Nanak Sagar catchment using GIS, remote sensing and MIF technique - AWARI, AISHWARYA; KUMAR, DHEERAJ; LAL, MOHAN (Journal of Soil and Water Conservation, 2024)
For the hill agrarians, water shortage is a major issue. Growing population and industrial growth have created a need for land for food and fodder, posing a challenge to the trade in land and water resources. The present study emphasizes the effectiveness of the integration of Weighted Overlay Index Analysis (WOIA) and Multi-Influencing Factor (MIF) techniques with Remote Sensing (RS) and Geographic Information System (GIS) in groundwater management, specifically in the delineation of the groundwater potential zones. This study uses various geo-environmental factors, such as lithology, geomorphology, land use/ land cover, the stream network density, slope and soil texture to identify the GWPZs and to classify the spatially distributed groundwater potential of the Nanak Sagar catchment, Uttarakhand. The WOIA is performed in ArcGIS, using the weights of different themes for delineation of the GWPZs of the basin. Results indicated that, out of 407.20 km2 area, 108.66 km2 (26.67 %) have very good potential while 124.77 km2 (30.62 %) have good potential for groundwater. Among the different geo-environmental factors, lithology, geomorphology and soil texture have decisive roles in the occurrence of groundwater of the basin. Thereafter, feasible methods for sustainable groundwater management are given.